Robust and High-Wettability Cellulose Separators with Molecule-Reassembled Nano-Cracked Structures for High-Performance Supercapacitors - Xiaoyu Wang; Wenqiu Zheng; Hui Zhao; Junying Li; Sheng Chen; Feng Xu (Nano-Micro Letters)
Highlights A robust and high-wettability cellulose separator with unique nano-cracked structures is constructed through hydrogen bond-driven reassembly of cellulose molecules using a green binary solvent. The nano-cracked structures endow the separator with high porosity (70.2%) and excellent electrolyte retention (329%). The supercapacitors with nano-cracked separators exhibit high specific capacitance (93.6 F g−1 at 1.0 A g−1) and a long cycling life (99.5% retention after 10,000 cycles).